Hubungan Karakteristik Pertumbuhan dan Komponen Hasil Beberapa Varietas Unggul Baru (Vub) Padi Pada Lahan Tadah Hujan di Kabupaten Aceh Besar - Khairani Sofia Harahap; Rizki Adriansyah; Amda Resdiar (Faculty of Agriculture University of Singaperbangsa Karawang, 2022)
The increased growth and production of rice plants that support agriculture is possible with the use of superior varieties of rain-shed land by viewing the linear relationship between two or more of the characteristics that influence the yield of plants. The purpose of this research activity sees the relationship between the characteristics of growth and the components of several new high-yield varieties of rice in the rain shed. The study was conducted from July - October 2021 on the agro-farm farm of farmers in the village of luthu lamweu, a prosperous district of aceh. Using a random group design with three varieties repeated three times, data analysis USES a correlation test. The observation of the varieties nutritii zinc is that there is a characteristic of growth that correlates positive and tangible with component results. The steady variety of plant characteristics and the number of malays are not manifest in component results. The logawa variety in the characteristic number of panicles correlated is not real to components of the rice crop. In the affirmative variety, the Logawa and the nutri zinc, which have a positive, tangible growth characteristic relationship to component results, is the nutrii zinc variety.